Training in high altitude environments and its influence on the changes in selected physiological indicators of a Slovak Republic representative in walking - Cillik, I.; Pupis, M. (Acta Universitatis Palackianae Olomucensis. Gymnica, 2005)
Middle and high altitude preparation is a longterm part of the preparation of our Slovak race walking representatives. Martin Pupiš is one of those athletes whose regularly makes use of this system. In our paper we report his preparation at four high altitude camps, in preparation phases in the years 1998/99-2001/02. The period of the year when the camps took place were very similar. Also the duration was from 26 days to 36 days. The average amount of racewalking and running was, for one day, approximately the same during all four camps. The proportion of race walking in kilometres increased from 70% to 80%. The proportion of walking zones changed depending on the current specialisation with the highest number of km in tempo endurance. The reaction to high altitude preparation was very good, when in analysed blood components - hematocrit, haemoglobin, erythrocytes, and a medium quantity of erythrocytes we recorded positive changes, and only in leucocytes was there a decrease.